2018
DOI: 10.1038/s41598-018-29489-1
|View full text |Cite
|
Sign up to set email alerts
|

Illness uncertainty, anxiety and depression in Chinese patients with glaucoma or cataract

Abstract: This study evaluated illness uncertainty, anxiety and depression among glaucoma patients and cataract patients in China. 263 patients with primary glaucoma and 100 patients with age-related cataract were recruited sequentially from Zhongshan Ophthalmic Center between October 2013 and March 2016. All the participants completed questionnaires for socio-demographic information, Mishel Uncertainty in Illness Scale (MUIS) and Hospital Anxiety and Depression Scale (HADS). 25 of the 263 glaucoma patients and 21 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 37 publications
2
45
1
5
Order By: Relevance
“…Although some previous studies have evaluated the possible benefit of cataract surgery on depression 13 , 15 23 , the results are controversial as some of these studies indicated that the depressive symptoms did not improve after cataract surgery 13 , 21 , 22 . Moreover, most of these studies had follow-up periods of < 1 year 13 , 15 23 , and only one was a population based study 16 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some previous studies have evaluated the possible benefit of cataract surgery on depression 13 , 15 23 , the results are controversial as some of these studies indicated that the depressive symptoms did not improve after cataract surgery 13 , 21 , 22 . Moreover, most of these studies had follow-up periods of < 1 year 13 , 15 23 , and only one was a population based study 16 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of cataract surgery on depressive symptoms remains controversial. Some studies have demonstrated the beneficial effects of cataract surgery on depression 15 20 , whereas others have suggested no remarkable impact 13 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not systemically investigated, the impairment of synaptic connections between neurons within the retina and the brain can potentially affect structural and functional integrity of RGCs and their axons. Interestingly, it was shown that genetic mutant Olfm2 in mouse was associated with abnormal psychological phenotypes such as anxiety and reduced levels of exploratory and locomotor activities[ 18 ], while ours and various other studies have shown that psychological conditions such as anxiety are strongly connected with the incidence of POAG[ 19 - 21 ] likely through reduced retrograde axonal transport of neurotropic factors, such as brain-derived neurotrophic factor. Taken together, OLFM2 is likely a candidate gene for POAG/JOAG.…”
Section: Discussionmentioning
confidence: 96%
“…In case of patients with non-diagnosed OAG the raise in IOP can lead to severe aggravation of the disease, which can pass unnoticed until advanced stages [19]. On the other hand, glaucoma patients may exhibit a wide array of psychiatric symptoms, as a consequence of progression of vision loss, such as depression [20], anxiety [21] and insomnia [22].…”
Section: Introductionmentioning
confidence: 99%